Clip-Domain Serine Protease Gene (LsCLIP3) Is Essential for Larval–Pupal Molting and Immunity in Lasioderma serricorne - Yang, Wen-Jia; Chen, Chun-Xu; Yan, Yi; Xu, Kang-Kang; Li, Can (Frontiers in Physiology, 2020)
Clip-domain serine proteases (CLIPs) play crucial roles in insect development and innate immunity. In this study, we identified a CLIP gene (designated LsCLIP3) from the cigarette beetle Lasioderma serricorne. LsCLIP3 contains a 1,773 bp open reading frame encoding a 390 amino acid protein and shows a conserved clip domain and a trypsin-like serine protease domain. Phylogenetic analysis indicated that LsCLIP3 was orthologous to the CLIP-B subfamily. LsCLIP3 was prominently expressed in larva, pupa and early adult stages. In larval tissues, it was highly expressed in the integument and fat body. The expression of LsCLIP3 was induced by 20-hydroxyecdysone (20E). A similar induction was also found by peptidoglycans from Escherichia coli and Staphylococcus aureus. RNA interference-mediated silencing of LsCLIP3 disrupted larval–pupal molting and specifically reduced the expression of genes in 20E synthesis and signaling pathway. The chitin amounts of LsCLIP3 RNAi larvae were greatly decreased, and expressions of six chitin metabolic-related genes were significantly reduced. Knockdown of LsCLIP3 increased larval sensitivity to Gram-negative and Gram-positive bacteria. There was significantly decreased of expression of four antimicrobial peptide genes. The results suggest that LsCLIP3 is an important component of the larva to pupa molt and for the immunity of L. serricorne.